Online Surveys as Data Collection Instruments in Education Research: A Feasible Option? - Minnaar, Lorinda; Heystek, Jan (South African Journal of Higher Education, 2016)
Using online surveys for research purposes appears to have gained international recognition as a convenient and cost-effective data collection method. The problem is that existing literature documenting the feasibility of this method in an education research context seems deficient. The question that emerges is “How feasible are Internet-based online surveys used as data collection instruments for educational research?” In the hope of expanding the scholarship, this article critically reflects on the successes and challenges encountered during the planning, design and activation phases of an online survey, used to collect data for a large-scale exploratory study with school governance and leadership as its overarching theme. Despite implementation of salient methodological considerations, the relatively low response rate alerts educational researchers to use online surveys as data collection instruments circumspectly.